TMEM16A is associated with voltage-gated calcium channels in mouse retina and its function is disrupted upon mutation of the auxiliary α2δ4 subunit - Caputo, Antonella; Piano, Ilaria; Demontis, Gian Carlo; Bacchi, Niccolò; Casarosa, Simona; Santina, Luca Della; Gargini, Claudia (Frontiers in Cellular Neuroscience, 2015)
Photoreceptors rely upon highly specialized synapses to efficiently transmit signals to multiple postsynaptic targets. Calcium influx in the presynaptic terminal is mediated by voltage-gated calcium channels (VGCC). This event triggers neurotransmitter release, but also gates calcium-activated chloride channels (TMEM), which in turn regulate VGCC activity. In order to investigate the relationship between VGCC and TMEM channels, we analyzed the retina of wild type and Cacna2d4 mutant mice, in which the VGCC auxiliary α2δ4 subunit carries a nonsense mutation, disrupting the normal channel function. Synaptic terminals of mutant photoreceptors are disarranged and synaptic proteins as well as TMEM16A channels lose their characteristic localization. In parallel, calcium-activated chloride currents are impaired in rods, despite unaltered TMEM16A protein levels. Co-immunoprecipitation revealed the interaction between VGCC and TMEM16A channels in the retina. Heterologous expression of these channels in tsA-201 cells showed that TMEM16A associates with the CaV1.4 subunit, and the association persists upon expression of the mutant α2δ4 subunit. Collectively, our experiments show a direct association between TMEM16A and the α1 subunit of VGCC. Close proximity of these channels allows optimal function of the photoreceptor synaptic terminal under physiological conditions, but also makes TMEM16A channels susceptible to changes occurring to calcium channels.